Soft budget constraints, European Central Banking and the financial crisis - Jannik Jäger; Theocharis Grigoriadis (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
During the European financial crisis, the European Central Bank implemented a series of unconventional monetary policy measures. We argue that these unconventional monetary policy measures created soft budget constraints for the Eurozone countries by lowering their bond yield spreads. This hypothesis is tested using pooled OLS estimations and two different datasets: monetary policy event dummies and the purchase volumes of the Securities Markets Programme (SMP). We find significantly negative effects on bond yield spreads for both datasets, leading us to accept the hypothesis. The results are confirmed by robustness checks that directly estimate the effect of unconventional monetary policy on central government debt.
Keywords: F34; F37; F42; P17; P51; 330; soft budget constraints; bond yield spreads; monetary policy events; securities markets programme; European Central Bank